Oscillation criteria for nonlinear second-order differential equations with damping - Çakmak, D. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
Some new oscillation criteria are given for general nonlinear second-order ordinary differential equations with damping of the form x?+?p?(?t?)?x?+?q?(?t?)?f?(?x?) = 0, where f is monotone or nonmonotone. Our results generalize and extend some earlier results of Deng.